Risk factors of seizure in childhood shigellosis: Seizure and shigellosis - Mahyar, Abolfazl; Mahyar, Shifteh; Oveisi, Sonia; Khajeh, Bahman; Khamenehpour, Khatereh; Chegini, Victoria; Dalirani, Reza; Enadi, Mojgan; Esmaeili, Shiva (Iranian Journal of Child Neurology, 2024)
Objectives: Shigellosis is one of the common causes of bacterial diarrhea in children. Seizures are common in shigellosis. It is essential to identify the risk factors of seizure in this disease. Materials & Methods This study was conducted on 224 children with shigellosis. The patients were divided into: With (case groups = 63 cases) and without seizures (control group = 161 cases). Groups were compared regarding different variables such as age, gender, clinical symptoms, and laboratory findings. Data analysis was done using statistical tests and SPSS software. Logistic regression analysis was used to determine the risk factors of seizures. Results Out of 224 cases of children with shigellosis, 107 (47.8%) were male and 117 (52.2%) female. Significant differences were observed between the two groups in terms of age, history of febrile convulsions, frequency of bloody diarrhea, frequency of fever, duration of diarrhea before hospitalization, abdominal pain, increase in BUN, hyponatremia, hypocalcemia, and red blood cell count in stool (P<0.05). Logistic regression analysis showed that a history of febrile seizure, fever, and hyponatremia are the risk factors for seizures in shigellosis Conclusion This study concluded that a history of febrile seizure, fever, and hyponatremia are risk factors for seizure in childhood shigellosis, thus rapid diagnosis and treatment of childhood shigellosis with risk factors is very important